Targeted Antibiotic Prophylaxis for Lung Transplantation in Cystic Fibrosis Patients Colonised with Pseudomonas aeruginosa Using Multiple Combination Bactericidal Testing - Helmy Haja Mydin; Paul A. Corris; Audrey Nicholson; John D. Perry; Gerard Meachery; Emma C. L. Marrs; Steven Peart; Christine Fagan; James L. Lordan; Andrew J. Fisher; Frances K. Gould (Journal of Transplantation)
Early infection is a recognised complication after lung transplantation in patients with cystic fibrosis (CF). Our centre uses multiple combination bactericidal testing (MCBT) when determining appropriate peritransplant prophylactic regimens. To evaluate our strategy, we compared the incidence of posttransplant infection in patients whose peritransplant antimicrobial regimens were determined using MCBT versus standard sensitivity testing. Patients with CF who were infected with Pseudomonas aeruginosa and underwent lung transplantations between 2000 and 2010 were included. Data was collected from clinical records and our microbiology database. Microorganisms cultured were mapped against antibiotic resistance, method of sensitivity testing, and antibiotics administered peritransplant. 129 patients were identified (mean age 28, male : female, 63 : 66). Fifty patients (38.8%) had antibiotics determined by MCBT. Two patients in the MCBT group developed septicaemia, 13 in the conventional group (P≤0.05, 2-tailed Fisher's test). Sepsis was attributable to P. aeruginosa in one patient from the MCBT group and seven patients in the conventional group (P=0.15). P. aeruginosa was recovered from the posttransplant pleural fluid of one patient who received MCBT-guided prophylaxis, six patients in the conventional group (P=0.25). Patients given antibiotics based on MCBT had significantly lower rates of septicaemia and lower rates of empyema.